DEVELOPMENT OF A MULTIMEDIA-BASED ELECTRONIC MAGAZINE ON BIOTECHNOLOGY MATERIALS FOR GRADE X SENIOR HIGH SCHOOL - Dini Kamilah Damanik; Irda Sayuti; Darmawati (Yayasan Amanah Nur Aman, 2026)
Rapid technological advancements require teachers and students to be able to utilize electronic learning media to clarify complex and abstract concepts. Biotechnology material for Grade X is considered interesting but relatively difficult to understand because it is multidisciplinary, abstract, and applicative in nature. Survey results indicate several problems, including students’ difficulties in understanding modern biotechnology, difficulty in memorizing bacterial names in Latin, and limitations of practical activities in schools due to constraints in time, equipment, materials, and laboratory facilities. This study aims to develop a multimedia electronic magazine as a solution to facilitate understanding of biotechnology material and to provide virtual practical experiences. This study employed a Research and Development (R&D) method using the ADDIE model, conducted up to the development stage. Expert validation resulted in an average score of 3.55 (very valid), the first-stage trial involving university students obtained a score of 3.74 (very good), and the second-stage trial involving students obtained a score of 3.55 (very good). In conclusion, the developed multimedia electronic magazine is of very high quality with an average score of 3.62 and can be implemented in Grade X senior high school biotechnology learning.